The Impact of N-Acetyl Cysteine and Coenzyme Q10 Supplementation on Skeletal Muscle Antioxidants and Proteome in Fit Thoroughbred Horses - Marisa L. Henry; Deborah Velez-Irizarry; Joe D. Pagan; Lorraine Sordillo; Jeff Gandy; Stephanie J. Valberg (MDPI AG, 2021)
Horses have one of the highest skeletal muscle oxidative capacities amongst mammals, which, combined with a high glycolytic capacity, could perturb redox status during maximal exercise. We determined the effect of 30 d of oral coenzyme Q10 and N-acetyl-cysteine supplementation (NACQ) on muscle glutathione (GSH), cysteine, ROS, and coenzyme Q10 concentrations, and the muscle proteome, in seven maximally exercising Thoroughbred horses using a placebo and randomized cross-over design. Gluteal muscle biopsies were obtained the day before and 1 h after maximal exercise. Concentrations of GSH, cysteine, coenzyme Q10, and ROS were measured, and citrate synthase, glutathione peroxidase, and superoxide dismutase activities analyzed. GSH increased significantly 1 h post-exercise in the NACQ group (p = 0.022), whereas other antioxidant concentrations/activities were unchanged. TMT proteomic analysis revealed 40 differentially expressed proteins with NACQ out of 387 identified, including upregulation of 13 mitochondrial proteins (TCA cycle and NADPH production), 4 Z-disc proteins, and down regulation of 9 glycolytic proteins. NACQ supplementation significantly impacted muscle redox capacity after intense exercise by enhancing muscle glutathione concentrations and increasing expression of proteins involved in the uptake of glutathione into mitochondria and the NAPDH-associated reduction of oxidized glutathione, without any evident detrimental effects on performance.